Investigation of a Possible Link Between Vaccination and the 2010 Sheep Pox Epizootic in Morocco. Issue 6 (9th March 2015) - Haegeman, A.; Zro, K.; Sammin, D.; Vandenbussche, F.; Ennaji, M. M.; De Clercq, K.
Summary: Sheep pox is endemic in most parts of Northern Africa and has the potential to cause severe economic problems. Live attenuated vaccines are used in Morocco, and in many other countries, to control the disease. Sheep pox virus (SPPV) re‐appeared in 2010 causing a nodular clinical form previously not observed in Morocco. The severe clinical signs observed during the course of this outbreak and initial reports citing similarity in nucleotide sequence between the Moroccan vaccine strain and field isolates warranted a more in depth analysis of this epizootic. In this study, sequence analysis showed that isolates obtained from four provinces of eastern Morocco were identical, demonstrating that a single SPPV strain was responsible for the 2010 epizootic. In addition, the genome fragments sequenced and phylogenetic analyses undertaken as part of this study showed significant differences between field isolates and the Moroccan vaccine strain. New PCR methods were developed to differentiate between wild‐type isolates and vaccine strains of SPPV. Using these methods, no trace of wild‐type SPPV was found in the vaccine and no evidence was found to suggest that the vaccine strain was causing clinical disease.